PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA GURU SMP NEGERI 18 PEKANBARU - Mariana H, Rina; Sasmita, Jumiati; Ningsih, Dewita Suryati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was conducted to determine how much influence the motivation and competence of the teacher’s performance of SMP Negeri 18 Pekanbaru. The population in this study were all full-time teacher at SMP Negeri 18 Pekanbaru. Sampling the authors use census methods and data analysis using multiple linear regression method. Based on the results of the study found that by testing simultaneously, variable motivation/ X1 and competency/ X2 si,ultaneously hae a significant impact on teacher performance SMP Negeri 18 Pekanbaru (Y). Testing of partially known variables of motivation/ X1 t-test value is 13,451 and variable competence/ X2 value is 8,385 t-test with a significance level of 0,000 is smaller than the 5 % level of confidence. This value is grater than t-table is 1,99. Can be concluded that the motivation variable/ X1 and competency/ X2 significantly affect the performance of SMP Negeri 18 Pekanbaru teacher (Y). Based on the above results it is known that the variables that most influence the performance of teachers of SMP Negeri 18 Pekanbaru is the motivation/ X1 Because it has the larget t valueKeywords: Motivation, Competence Teacher and performance